2018
DOI: 10.1097/cji.0000000000000207
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Esterification Enzyme Inhibition Enhances Antitumor Effects of Human Chimeric Antigen Receptors Modified T Cells

Abstract: Chimeric antigen receptor-modified T cell (CART) therapy has been demonstrated to have significant effect on hematologic tumor in patients. However, many persistent obstacles and challenges still limit the application. It is known that CD8 T cells are a key component of antitumor immunity. An avasimibe-induced inhibition of cholesterol esterification has been shown to improve the antitumor response of CD8 T cells in mice. In this study, using human CD19-directed CART cells as effector cells and CD19-overexpres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 43 publications
0
30
0
Order By: Relevance
“…CE accumulation might be related to the upregulation of caveolin-1, which promotes the gemcitabine-resistance. Furthermore, it is worth noting that a few recent studies have reported an enhanced antitumor activity of immune system when cholesterol esterification is blocked [ 31 , 32 ]. ACAT1 inhibitors was shown to increase plasma membrane cholesterol level and promote proliferation of CD8 + T cells [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CE accumulation might be related to the upregulation of caveolin-1, which promotes the gemcitabine-resistance. Furthermore, it is worth noting that a few recent studies have reported an enhanced antitumor activity of immune system when cholesterol esterification is blocked [ 31 , 32 ]. ACAT1 inhibitors was shown to increase plasma membrane cholesterol level and promote proliferation of CD8 + T cells [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…ACAT1 inhibitors was shown to increase plasma membrane cholesterol level and promote proliferation of CD8 + T cells [ 32 ]. Combination of avasimibe with immunotherapy, such as anti-PD-1 antibody therapy or chimeric antigen receptor-modified T cell therapy, show enhanced antitumor effects [ 31 , 32 ]. These results suggest that immune response plays an important role in avasimibe’s antitumor effects, and possibly in overcoming gemcitabine resistance in pancreatic cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to having direct effects on cancer cells, CE inhibition affects human chimeric antigen receptor-modified T cells. Administration of avasimibe augments the in vitro cytotoxic effect of these cells, an effect that can be partly explained by an increased ratio of cytotoxic CD8 T cells 114 . This observation is consistent with findings showing that avasimibe treatment effectively promotes CD8 effector T cell function 87,115 .…”
Section: Enhancement Of Cd8 T Cell Function and Inhibition Of The Regmentioning
confidence: 99%
“…TCR signal transduction is influenced by lipid metabolism, in part because non-esterified cholesterol is a major component of lipid rafts which localize TCR to sites of antigen presentation [ 10 , 11 ]. Acyl-coenzyme A:cholesterol acyltransferase 1 (ACAT1) is the dominant enzyme in CD8 + T cells that converts free cholesterol to cholesteryl esters and attenuates lipid raft formation [12] . ACAT1 deficiency leads to higher plasma membrane cholesterol levels in CD8 + T cells, and this correlates with higher TCR signaling levels after stimulation [13] .…”
Section: Implications Of All the Available Evidencementioning
confidence: 99%